The correlation between metacognitive skills and scientific attitudes towards the retention of male and female students in South Sulawesi, Indonesia - Romi Adiansyah; Aloysius Duran Corebima; Siti Zubaidah; Fatchur Rohman (International Journal of Evaluation and Research in Education (IJERE), 2021)
This was quantitative correlational research, which investigated the correlation between metacognitive skills and scientific attitudes towards the retention of male and female students in South Sulawesi, Indonesia. The research sample was biology education students in the second semester, with 104 students consisting of 47 males and 57 females. The instruments employed in this study were those for assessing metacognitive skills, scientific attitudes, and retention. Metacognitive skills and retention were measured using essay tests, while scientific attitudes were measured using observation sheets. The results indicated that the value of the simultaneous contribution of metacognitive skills and scientific attitudes towards to the retention of female students was higher than that of male students. The effective contributions of metacognitive skills and scientific attitude towards male students' retention were 3.33% and 24.67%. Metacognitive skills and scientific attitudes both contribute 14.5% and 17.2%, respectively, to female students’ retention.